Multilingual Publishing in the Social Sciences and Humanities: A Seven-Country European Study - Kulczycki, Emanuel; Guns, Raf; Pölönen, Janne; Engels, Tim C. E.; Rozkosz, Ewa A.; Zuccala, Alesia A.; Bruun, Kasper; Eskola, Olli; Starčič, Andreja Istenič; Petr, Michal; Sivertsen, Gunnar (My University, 2020)
We investigate the state of multilingualism across the social sciences and humanities (SSH) using a comprehensive data set of research outputs from seven European countries (Czech Republic, Denmark, Finland, Flanders [Belgium], Norway, Poland, and Slovenia). Although English tends to be the dominant language of science, SSH researchers often produce culturally and societally relevant work in their local languages. We collected and analyzed a set of 164,218 peer‐reviewed journal articles (produced by 51,063 researchers from 2013 to 2015) and found that multilingualism is prevalent despite geographical location and field. Among the researchers who published at least three journal articles during this time period, over one‐third from the various countries had written their work in at least two languages. The highest share of researchers who published in only one language were from Flanders (80.9%), whereas the lowest shares were from Slovenia (57.2%) and Poland (59.3%). Our findings show that multilingual publishing is an ongoing practice in many SSH research fields regardless of geographical location, political situation, and/or historical heritage. Here we argue that research is international, but multilingual publishing keeps locally relevant research alive with the added potential for creating impact.
Funding information: National Science Centre in Poland, Grant/Award Number: UMO‐2017/26/E/HS2/00019; European Cooperation in Science and Technology, Grant/Award Number: CA15137; Slovenian Research Agency, Grant/Award Number: P2‐0210; Flemish Government
Keywords: multilingualism; multilingual publishing; scholarly communication